Demystifying Touch n Go E-Wallet Acceptance using Technology Acceptance Model - Li, Wushuang; Hii, Puong Koh; Vijayakumaran, Naranthiran; Nurain, Ahmad; Goh, Chin Fei; Tan, Owee Kowang (Business Management and Strategy, 2023)
This study examines the determinants of behavioral intention to use Touch n Go e-wallet. The survey was completed by two hundred and fifty respondents measuring six variables, which includes behavioral intention (BI), perceived usefulness (PU), perceived ease of use (PEOU), subjective norm (SN), perceived trust (PT) and perceived risk and security (PRS). Partial Least Squares Structural Equation Modelling (PLS-SEM) was used as the main technique for data analysis. The results of this study showed that all constructs were significant in explaining behavioral intention to use e-wallets, except perceived risk and security. This study provides an opportunity to explore the effectiveness of providing a better experience and convenience of e-wallet services in the Malaysian context.